La ville maudite de Zarathoustra or l'Apocalypse de la modernité (2007)
Zarathustra's character in the Nietzschean text discovers the peculiarity of a rejection of the city and urban life. To think about this refusal is also to show the paradoxical field of Nietzsche's thought, from the historical context, although the 19th c